2015
DOI: 10.1002/dvg.22875
|View full text |Cite
|
Sign up to set email alerts
|

Grhl2 is required in nonneural tissues for neural progenitor survival and forebrain development

Abstract: Grainyhead-like genes are part of a highly conserved gene family that play a number of roles in ectoderm development and maintenance in mammals. Here we identify a novel allele of Grhl2, cleft-face 3 (clft3), in a mouse line recovered from an ENU mutagenesis screen for organogenesis defects. Homozygous clft3 mutants have a number of phenotypes in common with other alleles of Grhl2. We note a significant effect of genetic background on the clft3 phenotype. One of these is a reduction in size of the telencephalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…However, despite careful examination of numerous brain sections at multiple embryonic timepoints, we could not detect any Grhl2 expression within the developing mouse brain. These results indicate both of evolutionary divergence from the zebrafish, and suggest that the previously reported apoptosis of neural progenitors in murine models is due to a secondary effect, perhaps through defects in the overlying surface ectoderm (Menke et al, ), where Grhl2 is robustly expressed (Auden et al, ).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…However, despite careful examination of numerous brain sections at multiple embryonic timepoints, we could not detect any Grhl2 expression within the developing mouse brain. These results indicate both of evolutionary divergence from the zebrafish, and suggest that the previously reported apoptosis of neural progenitors in murine models is due to a secondary effect, perhaps through defects in the overlying surface ectoderm (Menke et al, ), where Grhl2 is robustly expressed (Auden et al, ).…”
Section: Discussionsupporting
confidence: 56%
“…Grhl1 had not been previously implicated in mediating neural function, and in concordance with this, we did not detect any expression of Grhl1 within the murine brain in the present study. Previous studies had shown that disruption of Grhl2 led to increased apoptosis of neural progenitors (Menke et al, ), although Grhl2 expression within the brain proper was not examined. Our previous work in zebrafish also showed that the fish orthologue of mouse Grhl2 , grhl2b was expressed within the vertebrate brain, and that transient grhl2b inhibition led to significantly elevated apoptosis at the midbrain‐hindbrain boundary (Dworkin et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent publications have demonstrated the essential functions of GRHL2 in development and differentiation with conflicting evidence on its role in EMT, and cancer progression 25,52,26 . A strong correlation of GRHL2 expression with various epithelial cells, undifferentiated progenitor cells, and chronic disease states such as atopic dermatitis and psoriasis were described 53,54 . Uniquely, hepatocytes are a rare subset of epithelial cells that do not normally express GRHL2 26 .…”
Section: Discussionmentioning
confidence: 99%
“…We identified the primary ciliary dyskinesia only (Pcdo) mutant in a mouse ENU mutagenesis forward genetic screen for recessive alleles leading to organogenesis phenotypes. ENU mutagenesis was performed as described previously (Stottmann, Moran et al 2011, Stottmann and Beier 2014, Menke, Cionni et al 2015, Lukacs, Roberts et al 2019) and phenotyping to recover mutant alleles was performed at early postnatal stages as part of an experiment to look for mutants with abnormal forebrain development. Pcdo mutants were initially identified by enlarged head and distended lateral ventricles upon gross dissection.…”
Section: Pcdo Is a Nonsense Allele Of Spag17mentioning
confidence: 99%